(untitled) (Clinics, 2014)
OBJECTIVE: Minimally invasive methods are used as alternatives to treat leiomyomas and include uterine artery embolization, which has emerged as a safe, effective method. This study aims to evaluate the magnetic resonance imaging predictors for a reduction in leiomyoma volume in patients undergoing uterine artery embolization. METHODS: This prospective longitudinal study was performed at a university hospital. We followed 50 symptomatic premenopausal women with uterine leiomyomas who underwent uterine artery embolization. We examined 179 leiomyomas among these patients. Magnetic resonance imaging was performed one month before and six months after uterine artery embolization. Two radiologists who specialized in abdominal imaging independently interpreted the images. Main Outcome Measures: The magnetic resonance imaging parameters were the uterus and leiomyomas volumes, their localizations, contrast perfusion pattern and node-to-muscle ratio. RESULTS: Six months after treatment, the average uterine volume reduction was 38.91%, and the leiomyomas were reduced by 55.23%. When the leiomyomas were submucosal and/or had a higher node-to-muscle ratio in the T2 images, the volume reduction was even greater (greater than 50%). Other parameters showed no association. CONCLUSIONS: We conclude that symptomatic uterine leiomyomas in patients undergoing uterine artery embolization exhibit volume reductions greater than 50% by magnetic resonance imaging when the leiomyomas are submucosal and/or had a high node-to-muscle ratio in the T2 images.